OPINION OF A YOUNG GENERATION FROM POLAND AND CZECH REPUBLIC ABOUT ECOLOGY, FRESHNESS, HYGIENE AND OVERAL LEVEL OF LARGE-SCALE RETAIL STORES - Zotyková, Lucie (European Scientific Journal, ESJ, 2014)
The paper is focused on opinions of young people from Moravian-Silesian Region and the Pomeranian Region about issues related to shopping in large-scale retail stores and a comparison between them. The comparison is stressed on the importance perception of food selection criteria, level of freshness selling goods, cleanliness and hygiene of those outlets.